Larval Genomics as a Viable, Fisheries‐Independent Tool for Investigating Population Structure in Tropical Pacific Tunas - Jacob E. Jaskiel; Hannah E. Aichelman; Giulia Anderson; Louw Claassens; James E. Fifer; Christina M. Hernandez; Alexa K. Huzar; Joel K. Llopiz; Jan W. Witting; Sean P. Mullen; Randi D. Rotjan (Molecular Ecology, 2026)
Understanding how dispersal, life history, and environmental variability shape genetic connectivity in the open ocean remains a central challenge in evolutionary biology. Highly migratory marine predators like tunas have traditionally been considered genetically homogeneous across ocean basins, yet emerging genomic evidence suggests that cryptic population structure can persist even in species with high gene flow and large effective population sizes. We used 2bRAD sequencing of 348 larval and subadult skipjack ( Katsuwonus pelamis ), yellowfin ( Thunnus albacares ), and bigeye tuna ( T. obesus ) collected from the central Pacific across 7 years of sampling to examine species boundaries, population genetic information, genetic structure, and connectivity. Larval sampling revealed consistent spawning by all three species and enabled unbiased detection of genetic patterns prior to recruitment bottlenecks. We found strong divergence amongst species, no evidence of structuring within skipjack or bigeye, and a divergent yellowfin population detected in 2 consecutive sampling years north of American Samoa. Comparisons between larvae and subadults suggest that sampling early life history stages can be a valuable tool for assessing population genetic information before recruitment bottlenecks, selective harvest by fisheries, adult dispersal, and selective pressures acting on adult populations, thereby contributing novel insights to the research and effective management of these species. These results highlight how larval genomics can complement traditional population genomic studies of adult tunas and reveal fine‐scale structure in highly vagile species, providing new perspectives on connectivity in the open ocean.